Respuesta :
Step-by-step explanation:
- 22 = -8u + 6(u-7)
-22 = -8u + 6u - 42
8u - 6u = 22 - 42
2u = -20
u = -20/2
u = -10
Answer:
[tex] \boxed{ \boxed{ \mathrm{ \bold{ \blue{ - 10}}}}}[/tex]
Step-by-step explanation:
[tex] \mathrm{ - 22 = - 8u + 6(u - 7)}[/tex]
Distribute 6 through the parentheses
⇒[tex] \mathsf{ - 22 = -8u + 6u - 42}[/tex]
Collect like terms
⇒[tex] \mathrm{ - 22 = - 2u - 42}[/tex]
Swap the sides of the equation
⇒[tex] \mathrm{ -2u - 42 = - 22}[/tex]
Move constant to R.H.S and change it's sign
⇒[tex] \mathrm{ - 2u = - 22 + 42}[/tex]
Calculate
⇒[tex] \mathrm{ - 2u = 20}[/tex]
Divide both sides of the equation by -2
⇒[tex] \mathrm{ \frac{ - 2u}{ - 2} = \frac{20}{ - 2} }[/tex]
Calculate
⇒[tex] \mathrm{u = - 10}[/tex]
Hope I helped!
Best regards!